N-Acetylcysteine Alleviates D-Galactose-Induced Injury of Ovarian Granulosa Cells in Female Rabbits by Regulating the PI3K/Akt/mTOR Signaling Pathway - Jiawei Cai; Yunpeng Li; Bohao Zhao; Zhiyuan Bao; Jiali Li; Shaoning Sun; Yang Chen; Xinsheng Wu (MDPI AG, 2024)
The ovary plays a crucial role in the reproductive system of female animals. Ovarian problems such as ovarian insufficiency, premature aging, polycystic ovary syndrome, and ovarian cysts may lead to ovulation disorders, abnormal hormone secretion, or luteal dysfunction, thereby increasing the risk of infertility and abortion. Only when the ovarian function and other organs in the reproductive system remain healthy and work normally can female animals be ensured to carry out reproductive activities regularly, improve the pregnancy rate and litter size, promote the healthy development of the fetus, and then improve their economic value. The follicle, as the functional unit of the ovary, is composed of theca cells, granulosa cells (GCs), and oocytes. GCs are the largest cell population and main functional unit in follicles and provide the necessary nutrients for the growth and development of follicles. N-acetylcysteine (NAC) is a prevalent and cell-permeable antioxidant molecule that effectively prevents apoptosis and promotes cellular survival. Over the past few years, its function in boosting reproductive performance in animals at the cellular level has been widely acknowledged. However, its specific role and mechanism in influencing GCs is yet to be fully understood. The objective of this study was to examine the effects of NAC on ovarian damage in female rabbits. For this purpose, D-galactose (D-gal) was first used to establish a model of damaged GCs, with exposure to 1.5 mg/mL of D-gal leading to substantial damage. Subsequently, varying concentrations of NAC were introduced to determine the precise mechanism through which it influences cell damage. Based on the results of the Cell Counting Kit-8 assay, flow cytometry, and Western blotting, it was found that 0.5 mg/mL of NAC could significantly suppress cell apoptosis and promote proliferation. In particular, it decreased the expression levels of Bax, p53, and Caspase-9 genes, while concurrently upregulating the expression of the BCL-2 gene. Moreover, NAC was found to alleviate intracellular oxidative stress, suppress the discharge of mitochondrial Cytochrome c, and boost the enzymatic activities of CAT (Catalase), GSH (Glutathione), and SOD (Superoxide dismutase). RNA sequencing analysis subsequently underscored the critical role of the PI3K/Akt/mTOR pathway in governing proliferation and apoptosis within GCs. These findings demonstrated that NAC could significantly influence gene expression within this pathway, thereby clarifying the exact relationship between the PI3K/Akt/mTOR signaling cascade and the underlying cellular processes controlling proliferation and apoptosis. In conclusion, NAC can reduce the expression of Bax, p53, and Caspase-9 genes, inhibit the apoptosis of GCs, improve cell viability, and resist D-gal-induced oxidative stress by increasing the activity of CAT, GSH, and SOD. The molecular mechanism of NAC in alleviating D-gal-induced ovarian GC injury in female rabbits by regulating the PI3K/Akt/mTOR signaling pathway provides experimental evidence for the effect of NAC on animal reproductive function at the cellular level.